International debts of developing countries - Vladimír JENÍČEK (Agricultural Economics (AGRICECON), 2011)
The problem of international debts is, by its character, one of the most complex problems which the world economy is now facing. It complicates both the global balance of payments and the financial - credit system stability, with pronounced negative impacts on the currency stabilisation. It hinders the development of international economic co-operation and its higher forms - international economic integration. It is one of the reasons that the symmetrical forms of interdependence are pushed off and displaced by the asymmetrical ones. The global debts problem deteriorates, namely during the last time in interaction with the negative manifestations of the global problems (for example, at present very strongly with the environmental problems), the complex international co-operation climate.